2023
DOI: 10.3389/fmicb.2023.1121830
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effects of quercetin against foot-and-mouth disease virus in vitro and in vivo by inducing type I interferon

Abstract: Foot-and-mouth disease (FMD) is an acute contagious infectious disease that affects cloven-hoofed animals. Although current emergency FMD vaccines only take effect 7 days after vaccination, antiviral agents, such as quercetin, which is a common flavonoid, could reduce the spread of FMD virus (FMDV) during outbreaks. We investigated the in vitro and in vivo antiviral effects of quercetin against FMDV. Analysis of viral copy numbers showed that quercetin had a dose-dependent inhibitory effect on FMDV at concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 83 publications
(86 reference statements)
1
1
0
Order By: Relevance
“…Consistent with findings for other viruses [ 5 , 37 , 38 , 39 , 40 , 41 , 42 ], the analysis of the possible target affected in the cycle of JUNV multiplication through a time of addition assay showed that the greatest reduction in virus yields were obtained when QUER was present during the early stages of virus replication. However, the addition of the compound at delayed time points resulted in a minor but significant inhibition, indicating a possible secondary effect on a late stage of the virus cycle.…”
Section: Discussionsupporting
confidence: 82%
“…Consistent with findings for other viruses [ 5 , 37 , 38 , 39 , 40 , 41 , 42 ], the analysis of the possible target affected in the cycle of JUNV multiplication through a time of addition assay showed that the greatest reduction in virus yields were obtained when QUER was present during the early stages of virus replication. However, the addition of the compound at delayed time points resulted in a minor but significant inhibition, indicating a possible secondary effect on a late stage of the virus cycle.…”
Section: Discussionsupporting
confidence: 82%
“…In studies conducted by other groups, it was found that quercetin exhibits a dose-dependent inhibition of FMDV replication in vitro by inducing IFN production. It also demonstrates a significant antiviral effect during the early stages of FMDV entry and enhances the survival rate of FMDV-infected mice [ 25 ]; Moreover, quercetin has been shown to inhibit the replication of HCV and the production of infectious particles. It affects the integrity of viral particles, indicating a direct, host-mediated antiviral effect on HCV [ 26 ]; Similarly, quercetin has been observed to block BVDV infection at an early stage, inhibit BVDV replication, and ameliorate BVDV-induced histopathological damage by inhibiting oxidative stress or ERK phosphorylation [ 27 ].…”
Section: Discussionmentioning
confidence: 99%